ANALYSIS OF THE FORMATION OF TOXIC LANGUAGE OF MOBILE LEGEND ONLINE GAME STREAMERS ON THE YOUTUBE CHANNEL “TOP GLOBAL MIYA” (MORPHOLOGICAL STUDY) - romadhona, Ahlan; Afif Ardiansyah, Muhammad; Sancity, Nixie; Dwi Rohmah, Laili; Lulua, Lisa; Afkar, Taswirul (ASMARALOKA: Jurnal Bidang Pendidikan, Linguistik, dan Sastra Indonesia, 2025)
This research discusses the analysis of the formation of toxic language, morphological studies used by streamers of the online game Mobile Legend. This research aims to analyze the formation of toxic language which is often used when streamers play games on Bang Pascol's Top Global Miya YouTube channel. This research uses descriptive and analytical methods in the pronunciation of toxic language in YouTube content to obtain data. The results showed that toxic words, such as "stupid," "bujang inam," "dog," "cok," "tai," "pig," "pantek," "idiot," "fool," and "son of a bitch" ," has diverse origins and strong negative connotations. All of these words fall into the monomorphemic category, meaning they cannot be divided without losing meaning, and are often used to express anger, ridicule, or demean others.